A Study on The Utilization of Purple Sweet Potato (Ipomea batatas L) for Ice Cream as Antioxidants - Sudjatinah - Sudjatinah; Cornelius Hari Wibowo; Aldila Sagitaning Putri (Journal of Applied Food Technology, 2020)
The purposes of this study were to determine overrun, water content, anthocyanin and antioxidant content, and to find out the best formulations. The design used was completely randomized design (CRD) with a unidirectional pattern consisting of 5 treatments with 4 replications, while the treatment factor was the disticntion between ratio of sweet potato mash and water, as follows: P1: 50%: 50%; P2`: 60%: 40%; P3: (70%: 30%); P4: (80%:20%); P5: 90%: 10%. The observed variables were the content of water, overrun, anthocyanin and antioxidant activity. The results showed that the treatment had a significant effect (P <0.05) on the average water content, overrun and anthocyanin activity. The treatment did not have a significant effect (P> 0.05) on the average antioxidant activity. In conclusion : the ratio of purple sweet potato mash had a significant effect (P <0.05) on water content, overrun and anthocyanin, but it did not influence significantly (P> 0.05) on the antioxidant activity. Furthermore, the best ratio of water and purple sweet potato mash is 2:8 to produce a standard water content and overrun, anthocyanin levels and high antioxidant activity.